2015
DOI: 10.1136/archdischild-2015-308985
|View full text |Cite
|
Sign up to set email alerts
|

Dietary calcium intake influences the relationship between serum 25-hydroxyvitamin D3 (25OHD) concentration and parathyroid hormone (PTH) concentration

Abstract: Dietary calcium intake modifies the relationship between serum 25OHD concentrations and intact serum PTH concentrations. Thus, dietary calcium intake should be taken into account when assessing an individual's vitamin D status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 14 publications
1
25
1
Order By: Relevance
“…The serum 25(OH)D concentration usually is very low (< 15–20 nmol/l), unless a very low dietary calcium intake is the cause of the complaints. Serum PTH is elevated, but less so with a higher dietary calcium intake, than with a lower intake ( Patel et al, 2016 ). For the diagnosis, other causes of increased alkaline phosphatase should be excluded, such as Paget's disease or bone metastasis.…”
Section: Laboratory Examinationmentioning
confidence: 99%
“…The serum 25(OH)D concentration usually is very low (< 15–20 nmol/l), unless a very low dietary calcium intake is the cause of the complaints. Serum PTH is elevated, but less so with a higher dietary calcium intake, than with a lower intake ( Patel et al, 2016 ). For the diagnosis, other causes of increased alkaline phosphatase should be excluded, such as Paget's disease or bone metastasis.…”
Section: Laboratory Examinationmentioning
confidence: 99%
“…Attempts have been made to define vitamin D deficiency based on the 25(OH)D level at which PTH concentrations starts to rise. There are, however, several draw backs to this method: 1) the variation in the association between PTH and 25(OH)D is large thus making it difficult to detect an inflection point and 2) the relationship is influenced by dietary calcium intakes and requirements ( Djennane et al, 2014 ; Aloia et al, 2006 ; Patel et al, 2016 ). Many studies conducted in adults and adolescents have shown an inverse relationship between 25(OH)D concentrations and PTH, however the actual point of inflection at which PTH starts to rise is a point of considerable debate ( Aloia et al, 2006 ; Guillemant et al, 1999 ; Harkness and Cromer, 2005 ).…”
Section: Pathophysiology Of Nutritional Ricketsmentioning
confidence: 99%
“…Below these thresholds (in boys at 33–39 nmol/L and in girls at 20–37 nmol/L), 25(OH)D levels were positively associated with total BMD, and inversely associated with serum PTH and TRAP5b; whereas above these thresholds no relationships were found ( Wu et al, 2015 ). The influence of dietary calcium intake on the relationship between serum 25(OH)D concentrations and PTH levels was shown in healthy Indian adolescents, in whom those with higher than median dietary calcium intakes but with similar 25(OH)D concentrations to the control group had lower PTH concentrations while those with lower dietary calcium intake had higher PTH concentrations ( Patel et al, 2016 ). Similarly, Djennana et al emphasized the significant influence of a low calcium diet on the increase in PTH concentrations in children with 25(OH)D levels >50 nmol/L ( Djennane et al, 2014 ).…”
Section: Pathophysiology Of Nutritional Ricketsmentioning
confidence: 99%
“…[1314] Thus, it is a critical phase, wherein increased exposure to high fluoride with low dietary calcium intake and decreased serum 25 hydroxyvitamin D 3 (25OHD) concentration may have an impact on the bone and teeth mineralization. Therefore, the aim of this study was to examine: (a) the prevalence and association of dental and skeletal fluorosis in adolescents from different socioeconomic strata (SES) in an area endemic for fluorosis and (b) the association of dental and skeletal fluorosis with dietary calcium intake and serum 25OHD concentrations.…”
Section: Introductionmentioning
confidence: 99%